Release of Soluble Insulin Receptor From Neurons by Cerebrospinal Fluid From Patients With Neurocognitive Dysfunction and HIV Infection - Gerena, Yamil; Menéndez-Delmestre, Raissa; Delgado-Nieves, Andrea; Vélez, Joyce; Méndez-Álvarez, Jarold; Sierra-Pagan, Javier E.; Skolasky, Richard L.; Henderson, Lisa; Nath, Avindra; Wojna, Valerie (Frontiers in Neurology, 2019)
Previously we found that high levels of soluble insulin receptor (sIR) in the cerebrospinal fluid (CSF) of an HIV-infected women cohort were associated with the presence and severity of HIV-associated neurocognitive disorders (HAND). In this study we investigated if CSF from this population, HIV-1 Tat, and selected cytokines induces sIR secretion from human neuronal cells. Twenty-three (23) HIV-seropositive women stratified by cognitive status and five HIV- seronegative women were evaluated. Soluble IR levels were measured in the extracellular medium of neuronal cells (SH-SY5Y) that were exposed (for 24 hrs) to the CSF of patients. The levels of sIR, HIV-1 Tat, and cytokine levels (IL-2, IL4, IL-6, IFNγ, TNFα, and IL-10) were quantified in the CSF of participants by ELISA and flow cytometry. Neuronal secretion of sIR was measured after exposure (24hrs) to HIV-1 Tat (0.5 nM to 250 nM), or specific cytokines. The effects of TNFα and HIV-1 Tat on sIR secretion were also evaluated in the presence of R7050 (TNFα antagonist; 10 nM). Glucose uptake in cells exposed to HIV-1 Tat was monitored by flow cytometry using 2-NBDG fluorescent glucose (10 μM) in the presence of insulin (100 μM). Neurons exposed to the CSF of HIV-infected women had higher sIR levels according to the severity of neurocognitive impairment of the participant. Increased CSF sIR levels were associated with the presence and severity of HAND and were positively correlated with CSF HIV-1 Tat levels in HIV-infected women with cognitive impairment. CSF levels of IL-2, IFNγ, and TNFα were significantly increased with HAND. However, only TNFα (5 pg/mL) and HIV-1 Tat (100 nM) induced a significant increase in neuronal sIR secretion after 24hr exposure, an effect that was antagonized when each were combined with R7050. Our data suggests that TNFα and HIV-1 Tat from the CSF of HIV-infected women regulate the secretion of sIR from neuronal cells and that the effect of HIV-1 Tat on sIR secretion may depend on TNFα receptor activation.